The Malicious Football Game: Urban Interactions and Power Relations in Lourenço Marques, Capital of Colonial Mozambique - Domingos, Nuno (2015)
Focusing on the game of football performed in the outskirts of Lourenço Marques, the capital of colonial Mozambique, today's Maputo, the present article aims to demonstrate how the colonial situation in Mozambique during the last decades of Portuguese rule could be interpreted through the social and moral values that emerged from the dominant interactions in football matches. Association football is the grammatical basis for the construction of a particular language, which is the outcome of a contextual and porous adaptation to the surrounding colonial world, and is translated into the gestures and movements of football players, the individual cells of this shared idiom. In seeking to recover the contextual meaning of this language, this article will argue that the space of play, initially idealised as a locus of education by local African elites in the 1920s and 1930s, and afterwards criticised by colonial modernisers as a symptom of degeneration, possible political subversion and lack of economic productivity, was ultimately a field where the truth of the economy of symbolic practices and exchanges, which characterised everyday life in the suburbs of Lourenço Marques in the final stages of Portuguese rule in Mozambique, reigned.